Occupational Health Programs at PT. Barata Indonesia Cilegon - Endrixs Endrianto; Ahmad Zaelani Adnan; Ninin Asminah (Universitas Nahdlatul Ulama Surabaya, 2023)
Occupational health is a specific part of the health perspective focusing more on improving the quality of the workforce through implementing health efforts. This paper describes the occupational health programs in the Limited Liability Company (here and after called PT) Barata Indonesia Cilegon. This study was qualitative research using field observation and literature studies. The population was all workers at PT. Barata Indonesia, Cilegon, Banten Province. The data collection technique used was field observation. Then, the author descriptively examined occupational health programs using literature from theory, laws and regulations, ministerial regulations, and ministerial decrees. The results showed that the implementation of occupational health programs at PT Barata Indonesia Cilegon, among others, checking canteen facilities, medical checks up, gymnastics, giving Extra Fooding, HIPERKES, HIV/AIDS prevention policies, COVID-19 regulations, and a work environment that meets occupational hygiene and health requirements. In conclusion, PT Barata Indonesia Cilegon is very concerned about the occupational health of its workers. Therefore, PT Barata Indonesia Cilegon runs occupational health programs. PT Barata has made occupational health procedures so that they can be carried out following written procedures. The implementation of occupational health programs at PT Barata Indonesia Cilegon has been going well following the Republic of Indonesia Government Regulation Num. 88 of 2019 concerning occupational health.